Occupational ergonomics a practical approach - Stack, Theresa; Ostrom, Lee T. (Wiley, 2024)
The approach to the second edition remains the same which is analogous to a toolkit. The user will open the textbook and locate the tool that best fits the ergonomic assessment task he/she is performing. The chapters of the book progress from the concept of ergonomics, through the various assessment techniques, and into the more complex techniques. In addition to discussing the techniques, this book presents them in a form that the readers can readily adapt to their particular situation. Each chapter, where applicable, presents the technique discussed in that chapter and demonstrates how it is used. The supporting material at the end of each chapter contains exercises, case studies and review questions. The case study section of the book presents how to use techniques to analyze a range of workplace scenarios. This new edition builds on the success of the first edition and contains the essential information on ergonomics and WMSDs. It provides an in-depth discussion of how to fix commonly found issues related to ergonomics and also how to attack the more difficult, complex workplace and task issues. The new edition significantly reworks some of the outdated chapters while including new chapters on Exercise Physiology, Return on Investment, and Ergonomic Climate."--